Kajian Literatur : Gamifikasi di Pendidikan Dasar - Rosina Zahara; Gihari Eko Prasetyo; Dwi Mirza Yanti (SOKO GURU: Jurnal Ilmu Pendidikan, 2021)
Gamification, which refers to the use of game elements and mechanics in non-gaming contexts, has become an interesting research topic in education. The researcher presents a literature review on the use of gamification in education with the aim of investigating the impacts, benefits, challenges, and trends associated with the application of gamification in an educational context. This literature review identifies several significant advantages of implementing gamification in education. Recent trends in the literature review on gamification in education include the use of new technologies, such as artificial intelligence, virtual reality, and augmented reality. In addition, research has also shown that the integration of gamification with traditional curricula can improve understanding and retention of subject matter. In order to maximize the benefits of gamification in education, this literature review recommends the importance of developing solid pedagogy, collaboration between teachers and game designers, and student participation in the gamification design process. More research is needed to understand more deeply the long-term effects of using gamification in education as well as the best strategies to address the challenges associated with its implementation.